2016
DOI: 10.1002/stem.2299
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Polymer Scaffold Reveals the Self-Maintenance Strategies of Rat Glioma Stem Cells by Organization of the Advantageous Niche

Abstract: Cancer stem cells (CSCs) are believed to be maintained within a microenvironmental niche. Here we used polymer microarrays for the rapid and efficient identification of glioma CSC (GSC) niche mimicries and identified a urethane-based synthetic polymer, upon which two groups of niche components, namely extracellular matrices (ECMs) and iron are revealed. In cultures, side population (SP) cells, defined as GSCs in the rat C6 glioma cell line, are more efficiently sustained in the presence of their differentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Our previous cDNA microarray data for the expression of some ABC transporter genes (available in NCBI GEO repository #GSE72431) reveal that only ABCB1 gene is specifically upregulated in C6 glioma SP cells compared with MP cells approximately by 10.6-fold (SP:MP = 0.64:0.060), suggesting that the ability of SP cells to expel xenobiotics is mainly dependent on ABCB1 in C6 cells [25, 26]. In addition, it has been reported that ABCB1 is overexpressed in human glioma tissues and its expression level is strongly correlated with that of another glioma CSC marker CD133, suggesting the importance of ABCB1 in glioma CSCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous cDNA microarray data for the expression of some ABC transporter genes (available in NCBI GEO repository #GSE72431) reveal that only ABCB1 gene is specifically upregulated in C6 glioma SP cells compared with MP cells approximately by 10.6-fold (SP:MP = 0.64:0.060), suggesting that the ability of SP cells to expel xenobiotics is mainly dependent on ABCB1 in C6 cells [25, 26]. In addition, it has been reported that ABCB1 is overexpressed in human glioma tissues and its expression level is strongly correlated with that of another glioma CSC marker CD133, suggesting the importance of ABCB1 in glioma CSCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…To prove this possibility, mouse bone marrow-derived monocytes were cultured with SP-or MP-conditioned medium (SPor MP-CM). When monocytes were cultured in 10% FBS-DMEM alone, the number of monocytes was decreased by 4.85% after 4-day culture (Tabu et al 2016). The cell number was higher in the culture with SP-CM than that in MP-CM, and the effect of the CM was in a concentration-dependent manner, suggesting that CSCs promote the survival of bone marrow-derived monocytes via soluble factors more efficiently than non-CSCs ( Fig.…”
Section: Side Population Cells In C6 Glioma Promote Survival Of Bone mentioning
confidence: 99%
“…We and others have found that CSCs have a potential to create their own niche which helps maintain the CSC phenotype and promote tumor progression (Tabu et al . ; Ricci‐Vitiani et al . ; Korkaya et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, therapeutic strategies against CSCs are essential for the accomplishment of cancer eradication [3]. Other researchers have found that CSCs have a potential to create their own niche, which helps maintain the CSC phenotype and promote tumor progression [4,5].…”
Section: Introductionmentioning
confidence: 99%